Erythrocyte values, pulmonary arterial pressure and right ventricle weight in broiler chicken of two commercial lines under intensive breeding at sea level - Ocampo R., Jorge (2012)
The aim of the study was to determine the association between erythrocyte values, pulmonary arterial pressure and ventricular cardiac relationships in Cob-Vantress (CV) and Ross (R) lines under intensive breeding at sea level. It was used 61 birds of 35 days of age per line. Body weight (BW), hematocrit (Ht), hemoglobin (Hb), erythrocyte count (E), pulmonary arterial pressure (PaPm), and rates among weights of right ventricle/total ventricle (RV/TV), left ventricle/total ventricle (LV/TV), right ventricle/body weight (RV/ BW), left ventricle/body weight (LV/BW), and total ventricle/body weight (TV/BW). Birds of line CV showed that BW (2.201 kg) and LF/TV (0.822) were greater that in line R (2.060 kg and 0.793 respectively) (p<0.05), whereas line R showed greater values of Ht (29.39%), Hb (10.92 g/dl), RV/TV (0.207), RV/BW (0.753), and TV/BW (3.659) than CV (25.84%, 10.25 g/dl, 0.178, 0.615, and 3.462, respectively) (p<0.05). PaPm was statistically similar for both lines (CV: 15.96; R: 17.34 mmHg). The results showed that chickens of both lines had a good cardiopulmonary performance.